FATE OF MILK YIELD AND FERTILITY PARAMETERS IN HOLSTEIN DAIRY COWS SIMULTANEOUSLY EXPOSED TO ZEARALENONE, DEOXYNIVALENOL AND FUMONISIN B1 MYCOTOXICITY - cangir uyarlar; oktay yilmaz (Journal of Animal and Plant Sciences, 2024)
This study was planned to investigate the effect of zearalenone (ZEA), deoxynivalenol (DON) and Fumonisin B1 (FB1) on blood metabolites, milk yield, estrous activity, pregnancy rate and uterine health in 486 heads of Holstein dairy cows. For this purpose, the data collected from the animals were divided into the four periods as follows: feeding with non-contaminated diet for 30 days (pre-contamination period), contaminated diet for 60 days (contamination period), contaminated diet supplemented with mycotoxin adsorbent for 30 days (adsorbent period) and the diet after removing the contaminated feedstuffs for 30 days (non-contamination period). Each feedstuff was analysed in contamination period and at the beginning of the non-contamination period to determine the presence or absence of ZEA, DON and FB1 in the diet. The blood metabolic profile was assessed in 21 animals in 1-10 days in milk, selected through cluster random sampling method while milk yield, estrous activity, pregnancy rate and prevalence of metritis/endometritis were compared among all four periods. The milk yield (P≤0.001) and milk fat (P≤0.05) in the contaminated period were low as compared to other periods. The concentrations of beta-hydroxybutyric acid (p≤0.001), non-esterified fatty acids (P≤0.05), gamma-glutamyl transferase (P≤0.05), and blood urea nitrogen (P≤0.001) parameters were significantly higher, while the glucose (P≤0.001) and triglycerides (P≤0.05) were lower in the contamination period, as compared to adsorbent and non-contamination periods. The pregnancy rate through artificial insemination decreased significantly during the contamination period (P≤0.05) as compared to pre-contamination period. The overall pregnancy rate in the pre-contamination period was also significantly decreased as compared to the adsorbent and non-contamination periods (P≤0.001). The percentage of type III anestrus were significantly lower during the non-contamination period (P≤0.05). The percentages of cows with metritis during the non-contamination period was significantly lower (p≤0.05) as compared to the contamination period. It was concluded that the routine feed analysis was necessary to determine the presence of ZEA, DON and FB1. Moreover, mycotoxin binder supplementation and/or removing contaminated feedstuffs from the diet under mycotoxicosis conditions may prevent the severe negative energy balance and improve the milk yield and fertility parameters.
Keywords: DON; ZEA; Fuminosins; Metabolic Parameters; Milk Yield; Fertility; Holstein